PENGARUH KEMAMPUAN MANAJEMEN TERHADAP LABA PENGRAJIN SEPATU - harini, sri (Universitas Djuanda Bogor, 2011)
Profit is one of business successful indicators of an enterprise. The enterprise profit was affected by managerial capability of a businessman. This research aimed at revealing businessman potency and the effect of the managerial capability on profitability of shoe maker at Kecamatan Ciomas Kabupaten Bogor. The research method applied qualitative descriptive and correlation analyses. The research result concluded that shoe maker at Kecamatan Ciomas Kabupaten Bogor owned a potency to be developed based on natural, human, and technology resources as well as public acquisition and geographically as tourism area. In addition, the shoe maker owned a good managerial capability (human resource, financial, marketing, and operational managements). The managerial capability affected on profitability of shoe makers at Kecamatan Ciomas Kabupaten Bogor.